Effects of Tea Fixation Methods and Fermentation Time on Total Phenol, Caffeine Content, and Consumer Acceptance of Kombucha Tea - Cici Mahmuda; Pudji Astuti (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Serious health problems such as the risk of prediabetes, decreased immune function, hypertension, and digestive disorders are increasing among young people. This condition has increased public awareness of maintaining health. In response, various foods and beverages that support health have emerged, including green tea and its derivative product, kombucha tea,  which  can  be  an  alternative  to  address  these  health  issues.  This  study  investigated  kombucha  tea  produced  using different  fixation  methods  (panning  and  steaming)  and  fermentation  durations  (7  and  10  days)  on  total  phenolic content, caffeine content, and consumer preference. The analysis of total phenolic content and caffeine content employed a quantitative approach using an experimental method with a 2×2 factorial design and three replications. The research process included tea production using panning and steaming methods, followed by fermentation with starter culture and SCOBY for 7 and 10 days. Chemical analyses  were then  conducted to determine  total phenolic and caffeine contents, along with a hedonic test using a 9-point scale. Data were analyzed using Two-Way ANOVA followed by Tukey’s test for total phenolic and caffeine contents, while non-parametric Kruskal–Wallis and Mann–Whitney tests were used for hedonic  data  analysis.  The  results  showed  that  the  highest  total  phenolic  content  (1191.56  ppm)  was  obtained  from steaming  with  10  days  of  fermentation,  while  the  lowest  (677.22  ppm)  was  found  in  panning  with  10  days  of fermentation. The highest caffeine content (189.23 ppm) was observed in steaming with 7 days of fermentation, while the lowest (53.93 ppm) was found in steaming with 10 days of fermentation. The interaction between fixation method and  fermentation  duration  (p  <  0.05)  significantly  affected  total  phenolic  content,  caffeine  content,  and  consumer preference. The steaming treatment with 10 days of fermentation produced the highest total phenolic content (1191.56 ppm)  and  the  lowest  caffeine  content  (53.93  ppm);  however,  the  7-day  fermentation  treatment  was  preferred  by  the panelists.  Total  phenolic  and  caffeine  contents  did  not  significantly  affect  sensory  attributes  and  therefore  did  not influence consumer preference.